Semi-empirical control method of solid wastes of medium and high activity; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 3 - Izmestiev К. М.; Komarov Е. А.; Seleev I. N.; Gavrilov P. М.; Silaev М. Е. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа